Effects of tropical typhoon event on land-based nutrients sources fluxes in the semi-enclosed eutrophic Zhanjiang Bay coastal water, China - Zhang, Jibiao; He, Yingxian; Zhang, Peng; Xv, Fang (Frontiers in Marine Science, 2025)
Coastal eutrophication has become a persistent environmental crisis around world driven by human activities and climate change. Nowadays, frequent and intense tropical typhoon disturbances has strongly affected the distribution and composition of nutrients in the land-ocean interface, resulting in the eutrophication risk in coastal water. However, the mechanistic links between tropical typhoon and land-based sources transport have not been well understood due to the complex processes. In this study, nutrient concentration, composition and flux of three estuaries and one sewage outlet in Zhanjiang Bay (ZJB) were analyzed. Before the typhoon, the average concentrations of dissolved inorganic nitrogen (DIN), dissolved inorganic phosphorus (DIP) and dissolved silicate (DSi) in the land-based source of ZJB were 61.77 ± 28.56 μmol/L, 6.79 ± 4.61 μmol/L, and 113.26 ± 64.52 μmol/L, respectively. The average concentration of DIN decreased by approximately 41.8%, the average concentration of DIP increased by approximately 46.2%, and the average concentration of DSi increased by approximately 1.7% after Typhoon Kompasu made landfall. At the same time, the DIN/DIP and DIN/DSi of the land-based sewage outlets and estuary of ZJB after typhoon landfall were much smaller than the Redfield ratio, indicating different degrees of nitrogen limitation. In addition, significant spatial and temporal variations in nutrients fluxes were observed in land-based sources before and after the typhoon. Before the typhoon, the total input fluxes of DIN, DIP, and DSi in the estuary and outfall of land-based sources in ZJB were 9.98 × 104 mol/h, 1.38 × 104 mol/h, and 9.78 × 104 mol/h, respectively. In contrast, after the typhoon, the total input fluxes of DIN increased by 3.21 × 103 mol/h, the total fluxes of DIP decreased by 3.01 × 103 mol/h, and the total fluxes of DSi increased by 5.20 × 104mol/h. After the typhoon, the concentration, composition and flux of nutrients entering the sea from land-based sources changed significantly compared with those before the typhoon. Moreover, the nutrients fluxes model of discharge were established, which can estimate the input fluxes of DIN, DIP and DSi based on field investigation. This study reveals the effects of tropical typhoon event on the nutrients fluxes from land-based sources into the semi-enclosed ZJB, which provides a scientific basis for further research on the impacts of typhoons on nutrients enrichment in coastal waters, as well as deepening the understanding eutrophication of coastal ecosystem under climate change.